Role of tourism advertising campaigns in improving destination image - Mohamed, Ghada Abdallah; Alakhras, Hebatullah Atef; Khalil, Rasha Ahmed; Mohamed, Mohamed Ali (Goodwood Publishing, 2022)
Purpose: The current paper aims to study the role of tourism advertising campaigns in improving the destination image and to propose a framework for improving the effectiveness of these campaigns. Research Methodology: This study is a qualitative study and it relied on distributing a questionnaire to a random sample of specialists about advertising campaigns in the tourism sector at the Egyptian Ministry of Tourism. Results: There is a statistically significant effect of advertising campaigns in improving the destination image by defining the type of tourist image and how it can be converted from negative to positive by following the latest and appropriate advertising means to diversify that image. Limitations: The field study data was collected from January to April 2022, in which 135 questionnaires were distributed, and 110 usable answers were received, with a response rate of 81%. Contributions: The study provides instructions for workers in the field of advertising campaigns to follow modern methods when preparing advertising campaigns that increase tourist movement and create a good tourist image.